Understanding Citrus Growers Views on Protection Problems and Mitigation Strategies in Punjab, Pakistan - Khan, Muhammad Asad; Shahzad, Muhammad; Peerzado, Moula Bux; Riaz, Ayesha; Ali, Umair; Usman, Muhammad (Journal of Agriculture and Veterinary Science, 2024)
Increasing population pressure necessitates greater food production for a sustainable future, yet the prevalence of insect pests and diseases intensifies competition for critical resources. Pakistan has recorded substantial losses due to disease infestations, particularly affecting citrus crops. Citrus fruits are among the most widely cultivated and economically important agricultural commodities globally. However, s. However, various pests, diseases, and environmental factors significantly impact the production and quality of citrus fruits. This study aims to comprehensively analyze the major insects, diseases, and other factors that affect the protection of citrus crops, as well as the strategies that growers employ to mitigate these challenges. Therefore, the present study explored the major diseases, insects, and other factors affecting citrus protection. One hundred fifty respondents were selected using a Multistage random sampling technique under a survey-based research design. Findings indicate that most of the respondents were above the age of 40, and a significant portion of the population has education above the matriculation level. Citrus fruit fly, citrus leaf miner and psylla were the major insects affecting citrus protection. Citrus white fly, citrus caterpillar, citrus red scale, and citrus black fly also harm the citrus orchards. Findings also indicate that the major diseases affecting citrus protection were Citrus Canker, Gummosis, Citrus Melanose and Citrus Scab. Moreover, the study revealed that awareness about advanced protection practices, incomplete knowledge regarding the identification of insects and diseases, high cost of chemicals, poor quality of pesticides and unwise application of spraying were the major factors affecting citrus protection. This study also identifies that the coping strategies adopted by the growers to protect citrus were IPM practices, chemical control, biological control, insect control nets, use of resistant varieties, crop rotation and crop insurance.
Keywords: Major Diseases; Major Insects; Citrus Protection; Citrus Varieties; Mitigation Strategies